STUDI DESKRIPTIF PERILAKU KOMPLAIN DAN MOTIF KOMPLAIN PELANGGAN RESTORAN DI HOTEL X SURABAYA - Ruslan, Chandra (University of Surabaya, 2013)
Hotel X is one of star hotel at Surabaya, and almost of the guest is domestictourist. According to tghe interview with the secretary of manager showing that there ismany of complaint about the service of”X” Resto at “X” Hotel in Surabaya. The result ofpre test showing that there is 23 respondents who state that visited ”X” Resto at “X”Hotel in Surabaya. During June – September 2012., and there is 8 of respondents whostate felt unconfortable of the service but no complaint, and there are 10 of respondentswho state compalint. The purpose of this research is explaining the complint behavior at”X” Resto at “X” Hotel in Surabaya..The research design is decriptive which explore the customer complaint behaviorat ”X” Resto in “X” Hotel in Surabaya according the demographic data: age, educationlevel, household level, and gender. The number of samples are 102 samples. Dataanalysis method by statistic descriptive, crosstabulation, and chi square analysis.This research showing that according to the whole of complaint behavior, the topand the most aggree by consumer is warning to the family and frends. The lower ofcomplaint behavior is complaint to the consumers protection agency and the highestcomplaint motive is take problem solving. There is association among the complaintbahevior and age, education level, and gender